Морфогенез у рослин Trifolium ambiguum Bieb. на другому році життя в умовах культури - Solonenko, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
Main morphological structures that are developed in plants on the second year of life are described. Dependence of theis quantitative indexes from the level of nitrogenous nutrition of plant is shown.